The Sikhs of South Auckland : an anthropological and historical account of Sikh migration and resettlement in the Counties-Manukau districts of Auckland, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology - Taylor, Lesley John (Massey University, 2011)
Migration has always been part of the human endeavour. This aspect of human behaviour is often characterised as driven solely by an economic rationale in that individuals or families migrate in order to improve their economic well being. Because of this perspective most contemporary academic studies have focused on the economic push- pull factors of migration. However there has been little attention given to other dimensions such as normative family obligations, geographical dispersion of relatives and friends or historical depth of family migration that may facilitate or inhibit the migration and resettlement process. To delve into these differing paradigms I spent considerable time with the Sikh Community as a participant observer and conducted interviews both formally and informally with Sikh migrants. I explored their reasoning for migration and documented their initial and long term experiences here in New Zealand. I conclude that economic considerations, whilst important no longer play the dominant role, as espoused by neo-classical economic theorists. Rather it is factors such as clean air, weather patterns, infrastructure capability and political transparency that have eclipsed the importance of immediate and future economic considerations when considering, implementing or maintaining the migration process.
Keywords: Sikh migration; Sikhs, Auckland; Counties-Manukau; Sikh communities